Four types of loyalty in early modern central Asia : the Tūqāy-Timūrid takeover of greater Mā Warā al-Nahr, 1598-1605 - Welsford, Thomas (Brill's Inner Asian library, 2013)
In Four Types of Loyalty in Early Modern Central Asia, Thomas Welsford offers a bold new way of analysing the T?q?y-T?m?rids' accession to power at the turn of the seventeenth century.